2015
DOI: 10.18512/1980-6477/rbms.v14n2p167-181
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros Fisiológicos e Produtividade de Espigas Verdes de Milho sob Diferentes Lâminas de Irrigação

Abstract: RESUMO-O objetivo do trabalho foi avaliar a influência de diferentes lâminas de irrigação sobre alguns parâmetros fisiológicos do milho verde, como índice de área foliar (IAF) e teor de clorofila total, relacionando-os com a produtividade de espigas verdes e com a eficiência do uso da água. O experimento foi conduzido de setembro a novembro de 2009, em Teresina-PI, na Embrapa Meio-Norte, em um Argissolo Vermelho Amarelo eutrófico. A cultivar utilizada foi o híbrido duplo AG1051. O delineamento experimental foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
5
1
3
Order By: Relevance
“…Under the influence of the applied water regimes, the chlorophyll index reached the highest value when 50% of the ETc was used, in relation to the other regimes, showing that under the conditions of the present study the water deficit did not negatively affect this variable (Figure 10B). The opposite result to that of a study by [56], who found a reduction in the chlorophyll index following a reduction in the irrigation depth, for five irrigation depths at different sampling times.…”
Section: Source Ofcontrasting
confidence: 99%
“…Under the influence of the applied water regimes, the chlorophyll index reached the highest value when 50% of the ETc was used, in relation to the other regimes, showing that under the conditions of the present study the water deficit did not negatively affect this variable (Figure 10B). The opposite result to that of a study by [56], who found a reduction in the chlorophyll index following a reduction in the irrigation depth, for five irrigation depths at different sampling times.…”
Section: Source Ofcontrasting
confidence: 99%
“…O valor máximo obtido aos 59 DAE oscilou entre 0,55 (1,0 m* 1,0 m) e 3,04 (0,50 m * 0,25 m). Nascimento et al (2015), em estudo sobre a influência de lâminas de irrigação sobre parâmetros fisiológicos no milho verde para a mesma cultivar em estudo, obtiveram resultados semelhantes a este trabalho, com valores médios de IAF variando de 1,94 a 3,70 aos 58 dias após semeadura (DAS).…”
Section: Resultsunclassified
“…Por outro lado, Nascimento et al (2015), na região de Teresina -PI, obtiveram produtividade média de espigas verdes despalhadas de 8.465,62 Kg ha -1 com estande de 50.000 plantas ha -1 , efetuando duas adubações de cobertura a primeira por ocasião da sexta folha completamente desenvolvida e a segunda pela oitava folha completamente desenvolvida. Quando comparado ao presente estudo, representou decréscimo de 27% na produtividade (6.167 Kg ha -1 ) para a densidade de 40.000 plantas ha -1 (E P 0,50 * E L 0,50 m).…”
Section: Resultsunclassified
“…However, Sangoi et al (2012) and Kolling et al (2016) did detect significant differences in maize yield when comparing different plant distributions. These different findings in the literature can be attributed to meteorological variations between agricultural years, especially in conditions of irregularly distributed rainfall during the crop cycle (Sangoi et al, 2011), or water deficit conditions (Nascimento et al, 2015). Leaf area index (LAI) of maize subjected to four spatial variation distribution in the sowing line for several days after the emergence of the crop.…”
Section: Grain Yieldmentioning
confidence: 99%